Protective Predictors Associated With Posttraumatic Stress and Psychological Distress in Chinese Nurses During the Outbreak of COVID-19 - Xia, Lu; Yan, Yajun; Wu, Daxing (Frontiers in Psychology, 2021)
Background: The novel coronavirus disease 2019 (COVID-19) posed an unprecedented threat to Chinese healthcare professionals. Nevertheless, few studies notably focused on nurses’ mental health conditions and exploring protective factors to prevention. This study aimed to explore the prevalence and the predictive factors especially defensive predictors associated with posttraumatic stress and psychological distress in nurses during the COVID-19 pandemic. Methods: In this online study, 1728 nurses (approximately 77.5% came from the COVID-19 pandemic frontline) were included in the final analysis. Posttraumatic stress disorder checklist for DSM-5 (PCL-5) and Self-Reporting Questionnaire (SRQ) was used to assess posttraumatic stress and psychological distress. Results: The results demonstrated that the prevalence of posttraumatic stress and psychological distress in nurses throughout China between February 1, 2020 and February 13, 2020 was 39.12% and 24.36%, respectively. Multivariate logistic regression indicated that insomnia, high panic intensity, and high impact of the COVID-19 pandemic were risk predictors of posttraumatic stress and psychological distress in nurses. Married participants increased risk of 1.58 times to have posttraumatic stress when compared with the single. Frontline medical staff were more likely to suffer from psychological distress. The adequate exercise was a protective predictor of psychological distress (AOR=0.655, 95% CI=0.486-0.883), but not with posttraumatic stress. High-quality diet was a protective predictor of posttraumatic stress (AOR=0.112, 95% CI=0.037-0.336) and psychological distress (AOR=0.083, 95% CI=0.028-0.247). Conclusions: Our study revealed the prevalence and factors associated with posttraumatic stress and psychological distress in nurses during the COVID-19. Low panic intensity, low level of impact, satisfactory sleep, adequate exercise, and better diet were protective factors of posttraumatic stress and psychological distress. It indicated that we should monitor nurses’ psychological status (particularly those from the COVID-19 pandemic frontline) and increase protective factors associated with posttraumatic stress and psychological distress.